PERAN MENS REA DALAM SISTEM HUKUM: ANALISIS HUBUNGAN DENGAN PRINSIP ETIKA DAN KEADILAN - Humam Balya; Syukran, Muh. Zidni; Abrar, Abrar (AS-SALAM, 2025)
Abstract: The concept of Mens Rea has been the foundation of criminal law for centuries, yet its relevance in contemporary crime contexts is increasingly questioned. This research aims to critically analyze the limitations and weaknesses of the Mens Rea concept in modern criminal law systems, focusing on evidentiary challenges, inadequacy in collective crimes, and systemic bias. Using normative legal research methods with a conceptual approach, this study analyzes legal literature, court decisions, and contemporary theories of criminal responsibility. The findings reveal that the Mens Rea concept faces three major challenges: difficulty in proving criminal intent that relies on subjective judicial interpretation, inadequacy of individual concepts in handling corporate and collective crimes, and bias favoring perpetrators from higher economic classes. In the digital era and modern crimes such as cybercrime, corporate environmental pollution, and systemic corruption, traditional Mens Rea concepts cannot capture the complexity of motivations and distribution of responsibility. This research recommends criminal law system reform by adopting a hybrid approach that combines considerations of intent, action, and objective impact, as well as developing the concept of "corporate mens rea" and impact-based approaches as alternatives to ensure substantive justice in handling contemporary crimes. Keywords: Mens Rea, Legal Ethics, Criminal Justice, Criminal Responsibility, Law.